1995
DOI: 10.1007/bf00032248
|View full text |Cite
|
Sign up to set email alerts
|

Biological N2 fixation by heterotrophic and phototrophic bacteria in association with straw

Abstract: IntroductionAsymbiotic diazotrophs Straw components and their direct utilisation by diazotrophs Aerobic and anaerobic cellulose degradation N2 fixation in soils by bacteria using products of straw decomposition N2 fixation in flooded soils N2 fixation in dryland soils Factors affecting N2 fixation associated with straw Ways to enhance straw-associated N2 fixation Conclusions References AbstractMuch of the crop residues, including cereal straw, that are produced worldwide are lost by burning. Plant residues, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 77 publications
1
22
0
1
Order By: Relevance
“…In rice straw incorporated into the soil in spring, a peak of ARA was detected in the very early period in the first cropping season, which was probably associated with the vigorous decomposition of readily decomposable substrates such as soluble sugars and hemicellulose 11,16 . On the other hand, the second slight increase of ARA of rice straw during the drainage period in April before transplanting in the following season was possibly related to the presence of microaerophilic or aerobic-anaerobic interfacial conditions that may stimulate BNF 2,4 .…”
Section: Discussionmentioning
confidence: 99%
“…In rice straw incorporated into the soil in spring, a peak of ARA was detected in the very early period in the first cropping season, which was probably associated with the vigorous decomposition of readily decomposable substrates such as soluble sugars and hemicellulose 11,16 . On the other hand, the second slight increase of ARA of rice straw during the drainage period in April before transplanting in the following season was possibly related to the presence of microaerophilic or aerobic-anaerobic interfacial conditions that may stimulate BNF 2,4 .…”
Section: Discussionmentioning
confidence: 99%
“…As most of other microbial activities, BNF activity in cellulosic substrates is generally enhanced by higher temperatures and the optimum temperature seemed to range from 20 to 45ºC 6,13 . The results obtained in this study indicated that heterotrophic BNF is maintained to an extent similar to or higher than the decomposition rate of organic matter at a temperature as low as 15ºC.…”
Section: Discussionmentioning
confidence: 99%
“…Yes, it is cited in the text as follows p. 17, Line 422: "….observation by earlier workers (Roper and Ladha 1995), we also found that…" Each value on the line graph represents mean nitrogenase activity in roots of 12 plants from four replicated plots. Values that differ significantly (one-way ANOVA, P<0.01) on each line graph are followed by different letters.…”
mentioning
confidence: 88%